NADPH Oxidase 1 Mediates α-Synucleinopathy in Parkinson's Disease - Cristóvão, Ana Clara (Society for Neuroscience, 2012)
Accumulation of misfolded α-synuclein is the pathological hallmark of Parkinson's disease (PD). Nevertheless, little is known about the mechanism contributing to α-synuclein aggregation and its further toxicity to dopaminergic neurons. Since oxidative stress can increase the expression and aggregation levels of α-synuclein, NADPH oxidases (Noxs), which are responsible for reactive oxygen species generation, could be major players in α-synucleinopathy. Previously, we demonstrated that Nox1 is expressed in dopaminergic neurons of the PD animal models as well as postmortem brain tissue of PD patients, and is responsible for oxidative stress and subsequent neuronal degeneration. Here, using paraquat (PQ)-based in vitro and in vivo PD models, we show that Nox1 has a crucial role in modulating the behavior of α-synuclein expression and aggregation in dopaminergic neurons. We observed in differentiated human dopaminergic cells that Nox1 and α-synuclein expressions are increased under PQ exposure. Nox1 knockdown significantly reduced both α-synuclein expression and aggregation, supporting the role of Nox1 in this process. Furthermore, in rats exposed to PQ, the selective knockdown of Nox1 in the substantia nigra, using adeno-associated virus encoding Nox1-specific shRNA, largely attenuated the PQ-mediated increase of α-synuclein and ubiquitin expression levels as well as α-synuclein aggregates (proteinase K resistant) and A11 oligomers. Significant reductions in oxidative stress level and dopaminergic neuronal loss were also observed. Our data reveal a new mechanism by which α-synuclein becomes a neuropathologic protein through Nox1-mediated oxidative stress. This finding may be used to generate new therapeutic interventions that slower the rate of α-synuclein aggregation and the progression of PD pathogenesis.